Process Patterns of Bussiness Process Design - Edirisuriya, A.; Jayaweera, P.; Wikramanayake, G.N.; Johannesson, P. (My University, 2006)
It is recognized that business models provides ways to explore new business ideas and hence design and redesign operational business processes. Business model describes who are involved in the business and what resources are exchange between them. Process model on the other hand, shows ordering of exchange of resources, communication among agents to coordinate these resource exchanges. Process model is use to trace and coordinate value exchanges. The business model used in this work is e3-value model. The e3-value model was originally designed to support the explorations of new business networks. The paper contributes by addressing the research questions of identifying: e3-value model elements that needs to be mapped into the process model, essential sub processes that should be in a process model with respect to the e3-value model and nature of the process patterns. The paper provides answers to these research questions. The paper also discuss a method to transforms a business model to a process model in a systematic way. Such a method would provide support for traceability, evaluation of design alternatives. When two agents are exchanging resources in a value transaction, the order of exchange of resources would be vary from one business case to another business case. It depends on the contractual agreement setup between the involved business partners. The derivation of a process model from a business model is considered to be a nondeterministic design process. There would be different ways of achieving same goal. As such there would be different process models that achieve the same goal. Process patterns are ready made solutions to a certain problem in a specific problem domain. Process patterns are using as a candidate to build the process model. It is up to the designer to choose the appropriate patterns to construct process model. The selection is depends upon costs and benefits. He could compare the ...
Keywords: Bussiness process design